Modulation of CXCR4-Mediated Gi1 Activation by EGF Receptor and GRK2 - Neves, Maria (ACS Pharmacol Transl Sci, 2020)
[Image: see text] The CXCL12 chemokine receptor CXCR4 belongs to the GPCR superfamily and is often overexpressed in cancer, being involved in tumor progression and metastasis. How CXCR4 signaling integrates with other relevant oncogenic transduction pathways and the role of GPCR regulatory mechanisms in such contexts are not well-understood. Recent data indicate concurrent upregulation in certain tumors of CXCR4, EGF receptor (EGFR), and G protein-coupled receptor kinase 2 (GRK2), a signaling node functionally linked to both receptor types. We have investigated in a model system the effect of the EGFR and GRK2 status on CXCL12/CXCR4-mediated activation of Gi, the earliest step downstream of receptor activation. We find that overexpressed and activated EGFR reduces CXCR4-mediated Gi1 activation and that GRK2 phosphorylation at tyrosine residues is required to exert its inhibitory actions on CXCR4–Gi stimulation, suggesting a shared path of modulation. Our data point to a role for GRK2 in the crosstalk of the CXCR4 and EGFR signal transduction pathways in pathological contexts characterized by concurrent overactivation of these proteins.